2016
DOI: 10.1002/zaac.201600135
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide‐Coordination Polymers with Pyridinedicarboxylic Acids: Syntheses, Structures, and Luminescent Properties

Abstract: Five lanthanide coordination polymers (Ln‐CPs) based on pyridine‐dicarboxylate and lanthanide metal ions were synthesized and characterized, namely [Sm(pydc)(Hpydc)(H2O)5]·4H2O (1) (H2pydc = 2, 5‐pyridine‐dicarboxylic acid), [Ho(pydc)(Hpydc)(H2O)3]n·4nH2O (2), [Ce(pydc)(bdc)(H2O)]n (3) (H2bdc = 1, 4‐benzenedicarboxylic acid), [Nd2(dipic)3(H2O)3]n (4), and [Pr2Ag2(dipic)4(H2O)5]n·5nH2O (5) (H2dipic = 3, 5‐pyridine‐dicarboxylic acid). Complexes 1 and 2 display mononuclear structure and 1D zigzag chains, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…The Ag I ion is coordinated to four nitrogen atoms from two distinct bpdc 2– ligands with Ag–N bond lengths of 2.173(7), 2.178(7), 2.592(8), and 2.685(8) Å and a N1–Ag1–N3 angle of 169.4(3)°, and these values are consistent with previously reported values for silver pyridyl compounds. [2a], Each thorium trimer is coordinated to six bpdc 2– ligands, which adopt two different coordination modes, namely, µ 3 ‐η 1 :η 1 :η 1 :η 1 :η 1 :η 1 bidentate chelating mode (Scheme c) and µ 5 ‐η 1 :η 1 :η 1 :η 1 :η 1 :η 1 monodentate bridging mode (Scheme d), through carboxyl oxygen atoms to form a chain of –[Th 3 (µ 3 ‐OH)(µ 2 ‐OH) 3 (µ 3 ‐bpdc) 3 –Th 3 (µ 3 ‐O)(µ 3 ‐OH) 3 (µ 5 ‐bpdc) 3 ] n –, which contains three strands of –[Th2‐(µ 3 ‐bpdc)‐Th1‐(µ 5 ‐bpdc) 2 ] n – left‐handed helical chains along the c direction with a pitch of 13.57 Å (Figure a and b). All of the helical chains in 2 are left‐handed and further bridged to each other along the ab plane by Ag I ions to form a 3D chiral framework (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ag I ion is coordinated to four nitrogen atoms from two distinct bpdc 2– ligands with Ag–N bond lengths of 2.173(7), 2.178(7), 2.592(8), and 2.685(8) Å and a N1–Ag1–N3 angle of 169.4(3)°, and these values are consistent with previously reported values for silver pyridyl compounds. [2a], Each thorium trimer is coordinated to six bpdc 2– ligands, which adopt two different coordination modes, namely, µ 3 ‐η 1 :η 1 :η 1 :η 1 :η 1 :η 1 bidentate chelating mode (Scheme c) and µ 5 ‐η 1 :η 1 :η 1 :η 1 :η 1 :η 1 monodentate bridging mode (Scheme d), through carboxyl oxygen atoms to form a chain of –[Th 3 (µ 3 ‐OH)(µ 2 ‐OH) 3 (µ 3 ‐bpdc) 3 –Th 3 (µ 3 ‐O)(µ 3 ‐OH) 3 (µ 5 ‐bpdc) 3 ] n –, which contains three strands of –[Th2‐(µ 3 ‐bpdc)‐Th1‐(µ 5 ‐bpdc) 2 ] n – left‐handed helical chains along the c direction with a pitch of 13.57 Å (Figure a and b). All of the helical chains in 2 are left‐handed and further bridged to each other along the ab plane by Ag I ions to form a 3D chiral framework (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of characteristic absorption bands at ν̃ = 1730–1690 cm –1 indicates that the carboxylate groups are coordinated completely to the metal centers in 1 and 2 . [5f], Moreover, a strong absorption peak at ν̃ = 1386 cm –1 for 2 indicates the presence of nitrate groups. [5e] These results are consistent with the results of the single‐crystal structural analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, IR spectra recorded after exposure to the flow-cell demonstrate some differences as compared to the spectrum of PDC solution (see Table 5, Fig. 5b, [65][66][67][68]). Band at 1724 cm -1 , attributed to C=O stretching vibration appears on spectra of wet Mg sample; bands in range of 1580 -1610 cm -1 attributed to asymmetric stretching modes of COOgroups [66,67] are shifted.…”
Section: Carboxylate Interaction With Corroding Mg By Vibrational Spectroscopymentioning
confidence: 88%
“…Analysis of IR spectra of CP-Mg342 (Fig. 5b) demonstrated that bands of carboxylates (COO -) were shifted as compared to the solution spectra (1607 -ν as , 1457 -ν s [68]). Band at 1724 cm -1 corresponding to C=O stretching of COOH, is absent in the PDC solution spectrum and appears in the spectrum of Mg sample, suggesting that the delocalization of electron density of carboxylic group disappears, instead the -(C=O)-Ois taking place; which can be schematically illustrated by a mechanism shown in Fig.…”
Section: Coordination Polymer Film Formation By 25-pyridinedicarboxylate (Pdc)mentioning
confidence: 99%
“…Choosing appropriate ligands to increase the excited state lifetime and quantum yield (the light output) of lanthanide(III) complexes is thus essential for the development of improved luminescent materials (Li and Yan, 2012). In this regard, aromatic carboxylic acids such as, terephthalic acid (Daiguebonne et al, 2008; Wang et al, 2012) benzene-carboxylic acids (Yan et al, 2005; Wang et al, 2010b, 2012; Zhuravlev et al, 2011; Gai et al, 2013), and pyridine-dicarboxylic acid (Reinhard and Güdel, 2002; Huang et al, 2008; Zhu et al, 2009; Song et al, 2016; Xiang et al, 2017; Kumar et al, 2018) have been particularly used to design luminescent lanthanide coordination polymers. A number of studies also exist on the complexes of aliphatic carboxylic acids such as, malonic acid (Hussain et al, 2019), succinic acid (Cui et al, 2005; De Oliveira et al, 2013), glutaric acid (Głowiak et al, 1987; Legendziewicz et al, 1999; Antic-Fidancev et al, 2002), and adipic acid (Wang et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%